ANALYSIS OF SANCTIONS FOR CRIMES AGAINST MORALITY (ZINA)IN ARTICLE 284 OF THE OLD CRIMINAL CODE AND ARTICLE 411 OF THE NEW CRIMINAL CODE: Perspectives on Islamic Criminal Law - Kamaludin, Alfin; Najmudin, Deden; Sumardi, Didi (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2026)
The change in the regulation of the crime of adultery from Article 284 of the old Criminal Code to Article 411 of the new Criminal Code raises questions about the basis for the renewal and effectiveness of the regulation of sanctions in the perspective of Islamic criminal law. This study aims to determine the regulation of the elements and sanctions of the crime of adultery in Article 284 of the old Criminal Code and Article 411 of the new Criminal Code, to analyze the views of Islamic Criminal Law on the regulation of sanctions of adultery in article 284 of the old Criminal Code and article 411 of the new Criminal Code, and to determine the effectiveness of the regulation of sanctions of adultery in the Criminal Code reviewed from the perspective of Islamic Criminal Law. This study uses normative juridical methods with legislative, conceptual, and legal reform approaches that are analyzed qualitatively normatively through literature studies. The results of the study show that Article 411 of the new Criminal Code expands the regulation of adultery compared to Article 284 of the old Criminal Code. From the perspective of Islamic criminal law, the arrangement is not fully in line with Islamic penal principles. In terms of effectiveness, Article 284 of the old Criminal Code is considered to be weak, while the new Article 411 of the Criminal Code shows a broader arrangement even though its application is still limited. The novelty of this study lies in the comparative analysis of the regulation of adultery in the old Criminal Code and the new Criminal Code which is associated with effectiveness based on court decisions in 2021–2025 and analyzed through the maqaṣid al-shari'ah approach. This research contributes to the development of criminal law studies through the analysis of the update of the regulation of the crime of adultery in the new Criminal Code. In addition, this study contributes to examining the conformity of the regulation of zina with the values of Islamic criminal law, this study also contributes to assessing the effectiveness of the regulation of the sanction of adultery, not only formally, but also in its application to the protection of morals, heredity, and honor.